Novel pathways to value nature: how guided forest bathing promotes new relationships with nature - Matteo Giusti; Annelie I Vårhammar; Vanessa A Masterson; Petra Ellora Cau Wetterholm (Ecology and Society)
Our relationship with nature adapts to our daily nature routines and it is rarely challenged. Forest bathing has been studied for its well-being benefits, but its potential as a novel nature-based activity to enrich human-nature relationships has not yet been examined. This multimethod study is based on 10 guided forest bathing sessions conducted in Sweden with 26 participants. Participants answered surveys before and after attending guided forest bathing sessions, and 16 of them were subsequently interviewed. Our results showed that these guided forest bathing sessions were mindful, restorative, and meaningful in deepening participants’ relationships with nature. With the guidance of session guides, participants engaged in novel interactions with nature, overcame challenges, and managed to identify, perceive, and treasure the value in them. Our findings underscore the importance of challenging conventional nature routines for enhancing well-being and sustainability.